Determination of Antioxidant Capacity, Flavonoids, and Total Phenolic Content in Eucalyptus and Clover Honeys - Ciappini, María C.; Stoppani, Fernando S. (Journal of Apicultural Science, 2014)
Polyphenolic compounds reportedly produce physiological effects that are beneficial to health. Bee products are particularly rich in polyphenolic compounds. We determined the antioxidant capacity and the phenolic and flavonoid compounds content of 81 samples of honey. We used the Folin-Ciocalteu reagent method to evaluate the total phenolic content. The antioxidant activities were evaluated using in vitro scavenging assays of 2,2-diphenyl-1-picrylhydrazyl (DPPH ) and hydroxyl radicals (OH ), Trolox equivalent antioxidant capacity (TEAC ), and ferric-reducing antioxidant capacity (FRAC ). Total phenolic content ranged from 40.3 to 193.0 mg gallic acid equivalents (GAE )/100 g; the flavonoid content varied from 1.4 to 7.5 mg quercetin equivalents (QE)/100 g. Eucalyptus honeys exhibited significantly higher phenolic content and free radical-scavenging activity than clover honey samples (p<0.05 for all). Principal component analysis explained 73% of the differences observed in antiradical activity with respect to floral origin. Total phenolic content may be more useful than the radical-scavenging assay for detecting antioxidant capacity in honey; it also represents the variable that most appropriately discriminated among these honeys.